Segmented Classification of Traffic Environments Using RGB-D Data: Considering the effect of image resolution and the relevance of artificial data during training - Lindgren, Johannes; Odehnal, Florian (My University, 2020)
In this thesis a method based on previous approaches to perform semantic segmentation using color (RGB) and depth images together (RGB-D) in a Convolutional Neural Network (CNN) is presented. To improve the accuracy of the prediction a fusion module is proposed, to fuse RGB and depth features more efficiently. Furthermore, it is proved that higher resolution images improve the accuracy of the segmentation, especially for thin structures that are far away. The drawback of increasing the image resolution, on the other hand, is that the runtime increases. The method is tested using both simulated and real-world data. It is concluded that training the network on artificial data only and then evaluating it using realworld data does not yield a good result due to differences in composition between data. Thus using only artificial data during training is not sufficient. Even though the artificial data can be used for pre-training the network, it is concluded that it does not increase the accuracy compared to training the network using only realworld data. It is shown that the use of depth images improves the robustness of the segmentation with a large margin. Finally, it is concluded that for this approach to yield its full potential, high-accuracy depth images are a requirement.
Keywords: Semantic Segmentation; Convolutional Neural Networks; Deep Neural Networks; Deep Machine Learning; Computer Vision; RGB-D Data